4x-3(x-2)=2(x-1)

Simple and best practice solution for 4x-3(x-2)=2(x-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x-3(x-2)=2(x-1) equation:


Simplifying
4x + -3(x + -2) = 2(x + -1)

Reorder the terms:
4x + -3(-2 + x) = 2(x + -1)
4x + (-2 * -3 + x * -3) = 2(x + -1)
4x + (6 + -3x) = 2(x + -1)

Reorder the terms:
6 + 4x + -3x = 2(x + -1)

Combine like terms: 4x + -3x = 1x
6 + 1x = 2(x + -1)

Reorder the terms:
6 + 1x = 2(-1 + x)
6 + 1x = (-1 * 2 + x * 2)
6 + 1x = (-2 + 2x)

Solving
6 + 1x = -2 + 2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2x' to each side of the equation.
6 + 1x + -2x = -2 + 2x + -2x

Combine like terms: 1x + -2x = -1x
6 + -1x = -2 + 2x + -2x

Combine like terms: 2x + -2x = 0
6 + -1x = -2 + 0
6 + -1x = -2

Add '-6' to each side of the equation.
6 + -6 + -1x = -2 + -6

Combine like terms: 6 + -6 = 0
0 + -1x = -2 + -6
-1x = -2 + -6

Combine like terms: -2 + -6 = -8
-1x = -8

Divide each side by '-1'.
x = 8

Simplifying
x = 8

See similar equations:

| 8j^2-32=0 | | 3h^2-12=0 | | 5x-2=10x-8 | | 2x*6= | | (4+x)(x-4)= | | x^3+3x^2-9x-8=0 | | y=x^3+3x^2+9x-10 | | 20x^2*5x*2=0 | | 6-x=4+x | | 6a+4a= | | ln(2x-9)=0 | | 9.6-y=7.2+2y | | 4p^2=-13p-3 | | 7=p+2q | | 2v-7=19 | | 100+34= | | 5x^2-8x=-5x+8 | | (3x^2+5x+7)-(2x^2-3x+10)= | | t^2-t=3t+21 | | w^2+7w=18 | | 6t^2+12t-90=0 | | 2c^2-10c=0 | | s^2+20s=0 | | 3+(x-2)=x+1 | | a^2-8a-20=0 | | a^2-8-20=0 | | v^2+4v-45=0 | | 0=2x^3+3x^2-36x-10 | | 4y-3=6+3(y-2) | | 3y-3=-13-7y | | 12b-4=2b-24 | | 4y-2+y+33=7y+40-5y |

Equations solver categories